Gender, nation and popular film in India : globalizing muscular nationalism - Sikata Banerjee (Routledge contemporary South Asia series, 2017)
nterpretations of manhood have unfolded in India within a middle class cultural milieu shaped by an assertive self-confidence fuelled by liberalisation, a process by which India has been integrated into the global political economy and the prominence of Hindutva or Hindu nationalist politics.